2008
DOI: 10.1017/s0007114508055657
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward genetic testing and personalised nutrition in a representative sample of European consumers

Abstract: Negative consumer opinion poses a potential barrier to the application of nutrigenomic intervention. The present study has aimed to determine attitudes toward genetic testing and personalised nutrition among the European public. An omnibus opinion survey of a representative sample aged 14 -55 þ years (n 5967) took place in France, Italy, Great Britain, Portugal, Poland and Germany during June 2005 as part of the Lipgene project. A majority of respondents (66 %) reported that they would be willing to undergo ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
119
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 18 publications
8
119
0
6
Order By: Relevance
“…In other words, personalised nutrition is a product of high perceived value for which a proportion of society is prepared to pay a premium. These findings align with those of previous survey studies of public attitudes toward personalised nutrition (Roosen et al, 2008;Stewart-Knox et al, 2009;Su and Lu, 2012) which have indicated that between one third and a half of Europeans would be keen to take advantage of personalised nutrition.…”
Section: Public Perspectives On Personalised Nutritionsupporting
confidence: 91%
“…In other words, personalised nutrition is a product of high perceived value for which a proportion of society is prepared to pay a premium. These findings align with those of previous survey studies of public attitudes toward personalised nutrition (Roosen et al, 2008;Stewart-Knox et al, 2009;Su and Lu, 2012) which have indicated that between one third and a half of Europeans would be keen to take advantage of personalised nutrition.…”
Section: Public Perspectives On Personalised Nutritionsupporting
confidence: 91%
“…If the results obtained during the research are compared with the data polled in the six European countries (STEWART-KNOX et al, 2009), then it is obvious that willingness to make a genetic testing is the lowest in Hungary among the tested countries. For example, in Portugal 48.5% of the respondents and in France 44.3% of them would have a genetic test made because they are generally interested.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there is increasing public interest in genetic testing in the health field, in a study investigating attitudes to genetic testing among 2000 individuals, 81 % of respondents believed that knowing their genetic risk could lead to better control of their lives (108) . A number of studies have reported that individuals identified as having a higher disease risk through genetic testing may be more motivated to change dietary habits (109)(110)(111) . Nevertheless a number of concerns towards genetic testing have been reported including cost, privacy, misuse of genetic information and fear that results could influence insurance companies and job opportunities (107,108,110,112) .…”
Section: Mechanism Of Mthfr C677t Polymorphism Riboflavin and Blood mentioning
confidence: 99%